EDUCATION BACKGROUND AND INNOVATION: IS CEOâS KNOWLEDGE HELPFUL FOR ENTREPRENEURIAL ORIENTED FIRMS TO INNOVATE? - Bela Shafira, Nabilla
A firm innovativeness is a clear indicator of competitiveness. For that reason, a firm must have skillful decision makers to accommodate the innovation process. As the strategic decision maker of the firm, the CEO uses their cognitive resources in the problem identification and problem-solving processes. Cognitive resources rooted in a person’s intelligence and can be developed by gaining knowledge, competence and experience. In addition, a firm can improve their innovativeness by applying entrepreneurial orientation. A firm with an Entrepreneurial Orientation (EO) exhibit practices, behaviors, and philosophies that emphasize innovative, risk-taking, and proactive actions. This research attempts to assess the influence of a CEO’s educational background on innovativeness of entrepreneurial oriented firm. I examine the proposed research questions using a sample of 154 European firms (chemical, pharma, materials). CEO educational background is measured by their knowledge width – the variety of academic majors achieved – and knowledge depth – education level and whether they have a degree in a firm-specific academic major. This research found that the CEO's depth of knowledge has a mixed influence towards firm innovativeness. The presence of firm-specific academic major in CEO's education background decreases firm innovativeness, while the higher education level increases a firm innovativeness. Keywords: